13 Effect of hypoxia on expression of the PP2A system in primary human cardiovascular cells: post-translation modification and involvement of hif1α. (1st April 1997) - Elgenaidi, I; Spiers, JP
Abstract : Dysregulation of protein phosphorylation has been linked to mechanical dysfunction and arrhythmias in a host of highly prevalent cardiovascular disorders. 1 Little is known about the effect of hypoxia on PP2A expression and regulation in the cardiovascular system. The aim of this work was to: (i) determine the expression profile of PP2A in different cardiovascular cells (HAEC, HASMC and HCF-av), investigate how this changes under hypoxia and following hydroxylase inhibition, (ii) study post-translational regulation of PP2A in HASMC under hypoxic conditions. HAEC, HASMC, and HCF-av were cultured in cell type specific media supplemented with growth factors. Following overnight attachment, the culture media was changed to one without growth factors, and the cells were culture for 24, 48 or 72 hour under normoxic or hypoxic (H24, H48, H72) conditions (1% O2, 5% CO2, and 94% N2 ) at 37°C or following exposure to DMOG (100 µM). Expression of mRNA was determined by semi-quantitative real time RT-PCR (comparative Ct method, 2 -ΔΔCt ) and expressed as fold increase following normalisation to GAPDH and GPI. Data are expressed as the mean±SEM and were analysed by Student's t-test or one-way analysis of variance (ANOVA) with post-hoc analysis (Bonferroni) as appropriate; p<0.05 indicates significance. The expression of PP2A transcripts under basal condition was lower in HASMC than HAEC and HCF-av except PPP2R3A, PPP2R4 and PPP2R5A. Hypoxia decreased the expression of PP2A transcripts in the three cardiac cells after 24, 48 and 72 hour (table 1). Total protein phosphatase activity was decreased (p<0.05) in both HASMC and HCF-av following hypoxia (24 hour) while no effect was observed in HAEC. Protein expression of the catalytic subunit of PP2A only decreased (p<0.05) after exposure to hypoxia for 72 hour in all cell lines. In HASMC, 24 hour hypoxia increased demethylated PP2CA and phosphorylated PP2CA abundance (p<0.05) and increased PME abundance (p<0.05). DMOG (100 µM) decreased both mRNA and protein Activity of PPP2CA. In conclusion, hypoxia suppresses the expression of PP2A in cardiac endothelial, smooth muscle and fibroblast with kinetics that are both cell and time dependent. In HASMC, hypoxia cause post-translational modification of PP2A attenuating its activity. Furthermore, prolyl-hydroxylase inhibition decreased PP2CA expression suggesting that HIF-1α may play a role in modulating the PP2A system during hypoxia in the cardiovascular system. Reference: 1. Swaminathan, Purohit, et al. J Clin Invest 2011;121:3277–8.